Effects of cutting strategy in the contour milling of open pocket AISI H13 with a low ratio thin-walled feature - Avicenna (Kulliyyah of Engineering,International Islamic University Malaysia, 2022)
In the pocket machining of hard material with a thin-walled structure, the selection of cutting strategy and conditions significantly influences the process, machined part, and tool condition outputs. Variations in cutting engagement variables, including cutting speed, feed rate, and depth of cut, could either significantly improve or deteriorate the cutting time components, machined part quality, and tool conditions to certain levels. This research combined the roughing and finishing operations in the pocket milling of hardened AISI H13 tool steel. Two consecutive cutting processes, with different contour tool paths, were integrated into a single operation (run) made for two distinct features of open pocket lateral wall and low-ratio thin-walled feature.